Compound dispersing agent for reducing viscosity of kaolin and preparation method thereof

CN122960049APending Publication Date: 2026-10-23CHINA KAOLIN CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611065962.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-17
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0009]本发明旨在解决现有高岭土分散剂降粘效果不佳、粘度浓度偏低的问题,提供一种可显著降低高岭土浆液粘度、提升其粘度浓度的复配分散剂及制备方法,通过多组分协同作用优化高岭土分散效果,适配造纸涂料的工业应用要求

Benefits of technology

有效改善国产高岭土粘度浓度不足的痛点,减少造纸企业对进口高岭土的依赖,在不改变高岭土原料品质的前提下,大幅降低生产能耗与干燥成本,经济效益突出。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122960049A_ABST
    Figure CN122960049A_ABST
Patent Text Reader

Abstract

The application discloses a compound dispersant for reducing the viscosity of kaolin and a preparation method thereof, and belongs to the field of deep processing of kaolin. The dispersant comprises the following components in parts by mass: 30-50 parts of sodium polyacrylate, 12-33 parts of sodium citrate, 10-35 parts of sodium silicate, 20-30 parts of sodium lauryl polyoxyethylene ether sulfate and 0.2-0.3 parts of sodium hydroxide. In the preparation, the first four components are dissolved in water, and the pH is controlled to be alkaline by adding sodium hydroxide solution dropwise to obtain a dispersant aqueous solution. The viscosity of kaolin slurry is significantly reduced by the synergistic effect of the multiple components, the viscosity concentration is up to 73.4%, the dispersing stability is high, the process is simple, and the compound dispersant is suitable for efficient dispersion of paper coating grade kaolin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of deep processing of kaolin in the paper and ceramics industries, and specifically to a compound dispersant for reducing the viscosity of kaolin and its preparation method. Background Technology

[0002] Kaolin is an important industrial raw material, a clay mineral composed of silicon-oxygen tetrahedra (SiO4) and aluminum-oxygen octahedrons (AlO2(OH)4) in a 1:1 ratio. Oxygen atoms are distributed in the base of the silicon-oxygen tetrahedra, while hydroxyl groups (-OH) are distributed on the inner surface of the aluminum-oxygen octahedrons. The oxygen atoms and hydroxyl groups form hydrogen bonds and align along the c-axis, thus forming the layered structure of kaolin. Due to the strong interlayer hydrogen bonding in kaolin, its overall properties are stable, and its crystal lattice is not prone to isomorphic substitution.

[0003] As a typical layered silicate mineral, kaolin possesses excellent physicochemical properties such as adsorption, plasticity, and stability, and its low raw material cost makes it widely used in ceramics, papermaking, rubber, lubricants, and fine chemicals. Among these, the rheological properties of kaolin, especially its viscosity, are the core parameters determining its industrial application effectiveness. The viscosity of kaolin suspensions directly affects the energy consumption and efficiency of the production process, and simultaneously determines the quality stability of the final product.

[0004] In the paper industry, viscosity concentration is commonly used to characterize the viscosity properties of kaolin suspensions. It is defined as the kaolin solids content corresponding to a suspension viscosity of 500 mPa·s at 22°C after determining the optimal dispersant dosage. Higher viscosity concentrations result in lower pulp viscosity for the same solids content, effectively saving energy and shortening drying time. Currently, the viscosity concentration of domestically produced kaolin is typically 50-65%, while that of paper coating-grade kaolin is between 66-70%. In contrast, kaolin produced by companies in the United States and Brazil generally has viscosity concentrations exceeding 70%. Although my country has abundant kaolin reserves, the viscosity concentration of most products is insufficient to meet the high-end demands of modern paper coating, necessitating large-scale imports of paper-grade kaolin by domestic paper companies. Research indicates that factors such as particle size, specific surface area, geometry, and crystallinity of kaolin all affect its dispersibility in water. Therefore, elucidating the mechanisms by which these factors affect kaolin viscosity is of significant industrial value for the targeted regulation of kaolin viscosity characteristics.

[0005] In the prior art, patent CN120247047A discloses a method for increasing the viscosity concentration of kaolin by mechanical shearing and extrusion. This method uses physical means to peel off the flaky stacked kaolin particles and reduce the hydroxyl groups exposed on the surface of the stepped stacked structure. After three shearing and extrusion treatments, the viscosity concentration of kaolin can be increased from 68.79% to 71.04%. However, repeated extrusion can easily lead to excessively fine particles and agglomeration.

[0006] Patent CN103145139B discloses a viscosity reducer, which is composed of sodium hexametaphosphate, sodium polyacrylate, borax, sodium hydroxide and methylene blue, and can reduce the viscosity concentration of kaolin slurry with a particle size of less than 2μm and a content of more than 90% to more than 70.2%.

[0007] Patent CN100563968C discloses a urea intercalation modification method, in which urea, an intercalating agent, is added to kaolin powder in a screw conveyor using a frequency converter. The amount of urea added is 2 to 10% of the mass of the kaolin powder, which can produce a kaolin product with a viscosity concentration of 72 to 73%.

[0008] Based on existing literature on viscosity reduction in kaolin, it is known that the viscosity of kaolin suspension is influenced by multiple factors, including particle size and distribution, particle morphology, crystal order, and pH value. The most common industrial dispersion method is the addition of sodium hexametaphosphate for assisted dispersion. To overcome the limitations of traditional dispersants, this application uses the long-chain surfactant sodium lauryl polyoxyethylene ether sulfate to replace sodium hexametaphosphate, and prepares a novel dispersant that can increase the viscosity concentration of kaolin slurry. Compared to the sodium hexametaphosphate system, this compound dispersant, at the same addition amount, can more efficiently reduce the viscosity of kaolin slurry and significantly increase its viscosity concentration. Summary of the Invention

[0009] This invention aims to solve the problems of poor viscosity reduction effect and low viscosity concentration of existing kaolin dispersants, and provides a compound dispersant and preparation method that can significantly reduce the viscosity of kaolin slurry and increase its viscosity concentration. The synergistic effect of multiple components optimizes the dispersion effect of kaolin and is suitable for the industrial application requirements of paper coatings.

[0010] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A compound dispersant for reducing the viscosity of kaolin, comprising the following parts by mass: Sodium polyacrylate (DC) 30-50 parts; Sodium citrate 12-33 parts; 10-35 parts sodium silicate; 20-30 parts of sodium lauryl polyoxyethylene ether sulfate; Sodium hydroxide 0.2-0.3 parts.

[0011] Sodium hydroxide is an external reagent added dropwise during the preparation process to adjust the overall pH of the slurry.

[0012] Furthermore, this invention also discloses a method for preparing a compound dispersant to reduce the viscosity of kaolin, comprising: Step 1: Weigh the required mass fractions of sodium polyacrylate, sodium citrate, sodium silicate, and sodium lauryl polyoxyethylene ether sulfate; Step 2: Dissolve each component from Step 1 in water and stir to obtain an aqueous dispersant solution; Step 3: Add sodium hydroxide aqueous solution dropwise to the dispersant aqueous solution obtained in Step 2 to control the pH to be alkaline.

[0013] In a further technical solution, in step 2, the solid content in the dispersant aqueous solution is 10-20%, the stirring time is 10-30 min, and the stirring speed is 500-2000 rpm.

[0014] In a further technical solution, in step 3, the concentration of the sodium hydroxide aqueous solution is 6 mol / L.

[0015] In a further technical solution, in step 3, the pH is 7.0-9.0, and the acidity or alkalinity is tested by a pH meter.

[0016] In a further technical solution, in step 3, the amount of sodium hydroxide added is 0.2-0.3 parts.

[0017] A further technical solution uses high-purity water.

[0018] The method for testing the optimal dispersion amount and viscosity concentration of this invention is referenced in GB / T14563-2008 "Kaolin and its Test Methods".

[0019] The stability of different slurries was compared by sedimentation tests. The specific method was as follows: 20g of kaolin was placed in a beaker, and the corresponding mass of dispersant and high-purity water were added. A high-speed mixer was set to 2000 rpm and stirred for 10 minutes. The slurry was then transferred to a graduated cylinder with an inner diameter of 2cm and a measuring range of 50mL. After standing, the sedimentation rate was observed using the graduated cylinder scale.

[0020] The pH of kaolin slurry significantly affects its viscosity properties. The relationship between the apparent viscosity and zeta potential of the slurry when the kaolin solid content is 20% is shown in the attached figure. Figure 6 As shown. Before the ζ-potential test, the 20% solids content kaolin slurry was diluted 500 times. The diluent was the supernatant obtained after centrifuging the 20% solids content kaolin slurry, and the test results were taken as the average of three tests.

[0021] In the above scheme, sodium polyacrylate, sodium citrate, sodium silicate, sodium lauryl polyoxyethylene ether sulfate, and sodium hydroxide are the effective active ingredients, and the solid content refers to the percentage of the above effective ingredients in the total mass of the viscosity reducer.

[0022] In the above scheme, the composition of kaolin includes 51.22% silicon dioxide (SiO2), 41.239% aluminum oxide (Al2O3), 0.919% potassium oxide (K2O), 1.098% iron oxide (Fe2O3), 1.036% phosphorus pentoxide (P2O5), 0.354% magnesium oxide (MgO), 0.004% zinc oxide (ZnO), 0.459% titanium dioxide (TiO2), 0.178% calcium oxide (CaO), and 3.235% sulfur trioxide (SO3).

[0023] The XRD patterns of kaolinite from domestically produced materials and other countries or regions are attached to the above scheme. Figure 1 The structure of coal-bearing kaolinite is shown in PDF#78-2109. The (001) and (002) crystal planes correspond to positions of 12.41° and 24.97°, respectively. The interlayer spacing of the (001) crystal plane of kaolinite was calculated to be 0.71 nm. The thickness of each crystal plane of kaolinite was determined by calculating the half-width at half-maximum (HWHM) of (001) and (002) using XRD diffraction patterns.

[0024] By Scherrer's formula The calculations are performed, where K is 0.89, λ is the diffraction wavelength of the Cu target, and B is the full width at half maximum (FWHM). The calculated layer thicknesses perpendicular to the (001) and (002) crystal planes are D001 = 28.2 nm and D002 = 31.1 nm.

[0025] The scanning electron microscope for domestically produced kaolin used in the above scheme is attached. Figures 2-5 As shown, this is a layered structure formed by stacking hexagonal sheets, exhibiting a regular geometric nanosheet morphology with a thickness of approximately 30-50 nm. The width of the sheet surface is approximately 0.5-3.0 μm.

[0026] The terms “include,” “including,” and “have” used in this article are all open-ended, meaning they include but are not limited to.

[0027] Unless otherwise specified, the terms used herein generally have their ordinary meaning in the context of the art, the subject matter, and the specific context. Certain terms used to describe this case will be discussed below or elsewhere in this specification to provide additional guidance to those skilled in the art in describing this case.

[0028] This invention uses a compound of sodium polyacrylate, sodium citrate, sodium silicate, and sodium lauryl polyoxyethylene ether sulfate, and adjusts the pH of the system using sodium hydroxide. Compared with existing technologies, it has the following outstanding advantages and technical effects: 1. Significantly reduces viscosity, with a substantial increase in viscosity concentration. The compound dispersant of this invention can effectively reduce the viscosity of kaolin slurry, increasing the viscosity concentration of kaolin at 500 mPa·s to a maximum of 73.4%, which is far higher than the conventional level of 66%~70% for domestic kaolin, and reaches the viscosity concentration standard of imported kaolin from the United States and Brazil, fully meeting the requirements of high-end applications in paper coating.

[0029] 2. Synergistic effect of multiple components, resulting in extremely strong dispersion stability. Sodium citrate and sodium silicate can complex metal cations on the surface of kaolin particles, eliminating "edge-to-surface" flocculation of particles; sodium polyacrylate and sodium lauryl polyoxyethylene ether sulfate form a dual stabilizing effect of electrostatic repulsion and steric hindrance on the particle surface, significantly increasing the absolute value of ζ-potential, effectively inhibiting particle agglomeration, making the kaolin slurry settle more slowly and disperse more evenly, and greatly improving its static stability.

[0030] 3. Superior performance compared to traditional sodium hexametaphosphate By using sodium lauryl polyoxyethylene ether sulfate to replace the commonly used sodium hexametaphosphate in industry, the viscosity reduction efficiency is higher and the viscosity concentration is increased more significantly with the same amount of addition. This overcomes the limitation of the traditional sodium hexametaphosphate in dispersion effect, and the dispersion system is more suitable for the surface characteristics of kaolin.

[0031] 4. The preparation process is simple and suitable for industrial production. The preparation of dispersants only requires dissolution, stirring, and pH adjustment at room temperature and pressure. It does not require complex equipment or harsh conditions such as high temperature, high pressure, or mechanical shearing. It is simple to operate, has low energy consumption, good reproducibility, and can be mass-produced industrially.

[0032] 5. The system has strong pH adaptability, protecting the structure of kaolin. Adjusting the pH of the system to the optimal dispersion range of kaolinite (7.0~9.0) eliminates the need for strong acid or alkali treatment, does not damage the layered crystal structure of kaolinite, and preserves the original physicochemical properties of kaolinite while improving dispersibility.

[0033] 6. Enhance the application value of domestically produced kaolin and reduce industrial costs. It effectively addresses the problem of insufficient viscosity concentration in domestically produced kaolin, reduces paper manufacturers' reliance on imported kaolin, and significantly reduces production energy consumption and drying costs without altering the quality of the kaolin raw material, resulting in outstanding economic benefits. Attached Figure Description

[0034] Figure 1 The X-ray polycrystalline powder diffraction pattern of domestically produced kaolin; Figure 2 A scanning electron microscope (SEM) image of domestically produced kaolin. Figure 3 Image 2: Scanning electron microscope (SEM) image of domestically produced kaolin. Figure 4 Image 3: Scanning electron microscope (SEM) image of domestically produced kaolin. Figure 5 Image 4: Scanning electron microscope (SEM) image of domestically produced kaolin. Figure 6 A schematic diagram showing the relationship between viscosity, ζ-potential, and pH of a 20% solids content slurry of domestically produced kaolin. Figure 7 This is a schematic diagram of the particle size distribution of kaolin. Figure 8 This is a schematic diagram showing the relationship between viscosity and ζ-potential of domestically produced kaolin suspension with the addition of sodium lauryl polyoxyethylene ether sulfate. Detailed Implementation

[0035] The present invention will be clearly described below with illustrations and detailed description. Any person skilled in the art who understands the embodiments of the present invention can make changes and modifications based on the technology taught in the present invention without departing from the spirit and scope of the present invention.

[0036] The terminology used herein is for the purpose of describing specific embodiments only and is not intended to limit the scope of this work. Singular forms such as “a,” “this,” “this,” “the,” and “the” as used herein also include plural forms.

[0037] Example 1: Dispersant preparation: Step 1: Take 30g sodium polyacrylate, 20g sodium citrate, 30g sodium silicate, and 20g sodium lauryl polyoxyethylene ether sulfate.

[0038] Step 2: Dissolve the weighed reagent in 900 mL of high-purity water and stir at 500 rpm for 30 min using a high-speed mixer. The effective component of the dispersant accounts for 10% of the total mass of the viscosity reducer.

[0039] Step 3: Under real-time pH meter monitoring, adjust the pH to 8 with a 6 mol / L sodium hydroxide aqueous solution. The volume change caused by adding the sodium hydroxide aqueous solution is negligible, and the mass of sodium hydroxide contained in the system is 0.26 g.

[0040] Step 4: After the pH stabilizes in step 3, continue stirring at 500 rpm for 30 minutes.

[0041] Example 2: Dispersant preparation: Step 1: Take 25g of sodium polyacrylate, 25g of sodium citrate, 25g of sodium silicate, and 25g of sodium lauryl polyoxyethylene ether sulfate.

[0042] Step 2: Dissolve the weighed reagent in 900 mL of high-purity water and stir at 2000 rpm for 30 min using a high-speed mixer. The effective component of the dispersant accounts for 10% of the total mass of the viscosity reducer.

[0043] Step 3: Under real-time pH meter monitoring, adjust the pH to 8 with a 6 mol / L sodium hydroxide aqueous solution. The volume change caused by adding sodium hydroxide aqueous solution is negligible, and the mass of sodium hydroxide contained in the system is 0.28 g.

[0044] Step 4: After the pH stabilizes in step 3, continue stirring at 2000 rpm for 30 minutes.

[0045] Example 3: Dispersant preparation: Step 1: Take 20g sodium polyacrylate, 25g sodium citrate, 25g sodium silicate, and 30g sodium lauryl polyoxyethylene ether sulfate.

[0046] Step 2: Dissolve the weighed reagent in 900 mL of high-purity water and stir at 1000 rpm for 30 min using a high-speed mixer. The effective component of the dispersant accounts for 10% of the total mass of the viscosity reducer.

[0047] Step 3: Under real-time pH meter monitoring, adjust the pH to 8 with a 6 mol / L sodium hydroxide aqueous solution. The volume change caused by adding sodium hydroxide aqueous solution is negligible, and the mass of sodium hydroxide contained in the system is 0.27 g.

[0048] Step 4: After the pH stabilizes in step 3, continue stirring at 1000 rpm for 30 minutes.

[0049] Example 4: The steps are the same as in Example 1, except that the amount of high-purity water in step 2 is 400 mL. The effective component of the dispersant accounts for 20% of the total mass of the viscosity reducer. The mass of NaOH is 0.09 g.

[0050] Example 5: The steps are the same as in Example 2, except that the amount of high-purity water in step 2 is 400 mL. The effective component of the dispersant accounts for 20% of the total mass of the viscosity reducer. The mass of NaOH is 0.11 g.

[0051] Comparative Example 1: The kaolin raw material was not treated in any way, and its solid content at 500 mPa·s was directly tested, i.e., its viscosity concentration.

[0052] Comparative Example 2: The steps are the same as in Example 2, except that the 25g of sodium lauryl polyoxyethylene ether sulfate in step 1 is replaced with 25g of sodium hexametaphosphate. The amount of sodium hydroxide used is 0.22g.

[0053] Comparative Example 3: The steps are the same as in Example 2, except that the 25g of sodium lauryl polyoxyethylene ether sulfate in step 1 is replaced with 25g of sodium hexametaphosphate. In step 2, the reagents mentioned in step 1 are dissolved in 400mL of high-purity water. The amount of sodium hydroxide used is 0.13g.

[0054] The viscosity concentration test method is as follows: The viscosity test instrument used was NDJ-8s, and the optimal amount of dispersant and viscosity concentration were calculated in accordance with GB / T14563-2008.

[0055] The specific steps are as follows: Step 1: Add the amount of water and total amount of dispersant at the lowest viscosity value to the stirrer, and add 200g of sample while continuously stirring. After adding, stir at 2000r / min for 10min.

[0056] Step 2: Transfer the slurry to a tall beaker, select rotor No. 2 and test the viscosity η1 at a speed of 60 r / min. The solid content S1 can be calculated from the initial amount of reagent and water added.

[0057] Step 3: Transfer all the slurry after viscosity measurement back to the mixing container, add 10 mL of water, stir evenly, and measure the viscosity η2 again.

[0058] Step 4: Take a portion of the slurry, dry it thoroughly, weigh it before and after drying, and calculate the solid content S2.

[0059] The formula for calculating viscosity concentration X (%) is as follows: ; In the formula: η1 and η2 are the viscosity values ​​(mPa·s) before and after adding water in the above steps; S1 is the solid content (%) when measuring viscosity η1; S2 is the solid content (%) when measuring viscosity η2.

[0060] As attached Figure 6 As shown, the pH of the dispersion system affects the surface potential of particles in the kaolin slurry, thus affecting its dispersibility. (Refer to previous literature and appendices.) Figure 6 The experiment concluded that kaolin exhibits good dispersibility within a pH range of 8-10. The dispersant of this invention contains a weak acid salt, and the prepared dispersant solution itself is weakly alkaline. The NaOH solution is used to regulate the pH; in the embodiments of this invention, the pH is uniformly controlled at 8 to eliminate the influence of pH and facilitate the explanation of the functions of the other effective components.

[0061] Table 1. Differences in viscosity concentration between Examples 1-5 and Comparative Examples 1-3 As shown in Table 1, in Comparative Example 1 without any dispersant, the viscosity concentration of the kaolin slurry was only 38.2%. After adding the dispersant prepared by this method, the viscosity concentration of the kaolin slurry in Examples 1-5 all increased. Example 2 achieved the highest viscosity concentration of 73.4%. This indicates that the dispersant can effectively reduce the viscosity of the kaolin slurry.

[0062] Comparative Examples 2 and 3 show the replacement of sodium lauryl polyoxyethylene ether sulfate with sodium hexametaphosphate while keeping other conditions unchanged. The viscosity concentration of the kaolin decreased. This indicates that, with other dispersant components remaining constant, sodium lauryl polyoxyethylene ether sulfate can replace sodium hexametaphosphate to achieve a better viscosity-reducing effect.

[0063] To demonstrate the synergistic effect among the active components of the dispersant, and how the compounded formulation can effectively regulate the zeta potential of the slurry and enhance its dispersibility in the dispersion medium (high-purity water), this invention prepared slurries using dispersants obtained from all examples and comparative examples at a mass ratio of 1:20 between the active components of the dispersant and kaolin, i.e., 1g of dispersant solid and 20g of kaolin solid per 100g of slurry. The relationship between viscosity, zeta potential, and stability was tested.

[0064] The stability of different slurries was compared by sedimentation tests. Specifically, 20g of kaolin was placed in a beaker, and the corresponding mass of dispersant and high-purity water were added. A high-speed mixer was set to 2000 rpm and stirred for 10 minutes. The viscosity η was measured using a viscometer rotor No. 2 at a speed of 60 rpm.

[0065] Transfer the slurry to a graduated cylinder with an inner diameter of 1.5 cm and a measuring range of 50 mL. Let it stand for 4 hours, and observe the settling velocity using the graduated cylinder scale. The higher the scale reading at the stratification interface, the more stable the slurry.

[0066] The excess slurry prepared for the sedimentation experiment was used for the zeta potential test. The 20% solids content kaolin slurry was diluted 500 times. The diluent was the supernatant obtained after centrifuging the 20% solids content kaolin slurry. The test results were taken as the average of three tests. As shown in Table 2.

[0067] Table 2. Viscosity, ζ-potential, and settling velocity of kaolin slurry in each example and comparative examples 1-3. It can be seen that the more charge the particles in the slurry carry, the better their dispersibility in water and the lower their apparent viscosity. Due to the increased charge, the classical repulsive force between particles becomes stronger, making flocculation and aggregation less likely, and slowing down the settling velocity. Sodium lauryl polyoxyethylene ether sulfate, replacing sodium hexametaphosphate, works synergistically with the long-chain structure of sodium polyacrylate on the kaolin surface, enhancing the mutual repulsion between surfaces and improving the dispersion stability of kaolin slurry particles. Figure 8 This provides a visual demonstration that sodium lauryl polyoxyethylene ether sulfate can effectively reduce the viscosity of kaolin slurry. (See attached image.) Figure 8 As shown, with the increase of sodium lauryl polyoxyethylene ether sulfate content, the viscosity of the kaolin slurry decreases, while the absolute value of the surface potential increases. The addition of NaCl is to demonstrate that the concentrations of Na and Cl ions have a relatively small impact on the overall viscosity.

[0068] Figure 7 This is a schematic diagram of the particle size distribution of kaolin particles, with an average particle size of approximately 2.45 nm, which is consistent with the results of XRD and electron microscopy.

[0069] To further illustrate the interaction between the effective components of the dispersant, which synergistically reduces the viscosity of kaolin slurry, this method also provides Comparative Examples 4-7, each using sodium polyacrylate, sodium citrate, sodium silicate, and sodium lauryl polyoxyethylene ether sulfate as a single component dispersant. Corresponding tests were also conducted. The dispersant dosage, preparation steps, and process parameters of Comparative Examples 4-7 are the same as in Example 2. The results are shown in Table 3.

[0070] Table 3 Viscosity, ζ-potential, and settling velocity of the slurry in Comparative Examples 4-7 It can be seen that, compared with the various embodiments, the viscosity-reducing effect of the single-component comparative example is poor. Sodium citrate and sodium silicate, as small molecule dispersants, can increase the alkalinity of the slurry by electrolysis in water as weak acid salts. Kaolin itself contains some metallic cation impurities, mainly located at the edges. This leads to "edge-to-surface" flocculation between particles through electrostatic attraction. At this time, sodium and sodium silicate can act as complexing agents, complexing with the surface cations to achieve a masking effect. Sodium acrylate and sodium lauryl polyoxyethylene ether sulfate, as long-chain surfactants, can increase the zeta potential and increase the electrostatic repulsion between particles when adsorbed on the kaolin surface. At the same time, they form a structure with certain steric hindrance, protecting the internal particles and reducing flocculation and agglomeration caused by mutual collisions during dispersion in water. The combination of effective dispersant components achieves a synergistic effect and has a better viscosity-reducing effect than sodium hexametaphosphate of the same mass.

[0071] In summary, the dispersant developed in this invention, which uses sodium lauryl polyoxyethylene ether sulfate to replace sodium hexametaphosphate and is compounded with various chemical reagents, can significantly increase the viscosity concentration of kaolin suspension.

[0072] The above embodiments are only for illustrating the technical concept and features of the present invention, and are intended to enable those skilled in the art to understand the content of the present invention and implement it accordingly. They should not be construed as limiting the scope of protection of the present invention. All equivalent changes or modifications made in accordance with the spirit and essence of the present invention should be covered within the scope of protection of the present invention.

Claims

1. A compound dispersant for reducing the viscosity of kaolin, characterized in that: It contains the following components in parts by mass: 30-50 parts of sodium polyacrylate; Sodium citrate 12-33 parts; 10-35 parts sodium silicate; 20-30 parts of sodium lauryl polyoxyethylene ether sulfate; Sodium hydroxide 0.2-0.3 parts.

2. A method for preparing a compound dispersant to reduce the viscosity of kaolin, characterized in that: The method for preparing the compound dispersant for reducing the viscosity of kaolin as described in claim 1 includes: Step 1: Weigh out sodium polyacrylate, sodium citrate, sodium silicate, and sodium lauryl polyoxyethylene ether sulfate according to the required mass proportions; Step 2: Dissolve each component from Step 1 in water and stir to obtain an aqueous dispersant solution; Step 3: Add sodium hydroxide aqueous solution dropwise to the dispersant aqueous solution obtained in Step 2 to control the pH to be alkaline.

3. The method for preparing a compound dispersant for reducing the viscosity of kaolin according to claim 2, characterized in that: In step 2, the solid content in the dispersant aqueous solution is 10-20%, the stirring time is 10-30 min, and the stirring speed is 500-2000 rpm.

4. The method for preparing a compound dispersant for reducing the viscosity of kaolin according to claim 2, characterized in that: In step 3, the concentration of the sodium hydroxide aqueous solution is 6 mol / L.

5. The method for preparing a compound dispersant for reducing the viscosity of kaolin according to claim 2, characterized in that: In step 3, the pH is 7.0-9.

0.

6. The method for preparing a compound dispersant for reducing the viscosity of kaolin according to claim 2, characterized in that: In step 3, the amount of sodium hydroxide added is 0.2-0.3 parts.

7. The method for preparing a compound dispersant for reducing the viscosity of kaolin according to claim 2, characterized in that: The water used is high-purity water.

Citation Information

Patent Citations

  • Production technology of high viscosity kaolin

    CN100563968C

  • Viscosity reducer for improving viscosity of kaolin, and its preparation method

    CN103145139B

  • Treatment method for improving viscosity concentration of kaolin through shearing and extruding

    CN120247047A